Ru(II) Complexes Bearing O, O-Chelated Ligands Induced Apoptosis in A549 Cells through the Mitochondrial Apoptotic Pathway - Jincan Chen; Jie Wang; Yuanyuan Deng; Tao Wang; Tifang Miao; Chengpeng Li; Xianhong Cai; Ying Liu; Justin Henri; Lanmei Chen (Bioinorganic Chemistry and Applications)
Two new Ru(II) complexes containing O, O-chelated ligands, Ru(dip)2(SA) (Ru-1) and Ru(dmp)2(SA) (Ru-2) (dip = 4,7-diphenyl-1,10-phenanthroline; dmp = 2,9-dimethyl-1,10-phenanthroline; SA = salicylate) were synthesized to evaluate their cytotoxicity in vitro. These complexes were found to exhibit moderate antitumor activity to different types of human cancers, including A549 (human lung carcinoma), MCF-7 (breast cancer), HeLa (human cervical cancer), and HepG2 (human hepatocellular carcinoma) cell lines, but displayed low toxicity to human normal cell lines BEAS-2B (immortalized human bronchial epithelial cells) when compared with that of cisplatin. Further studies revealed that these complexes could induce apoptosis in A549 cells, including activating caspase family proteins and poly (ADP-ribose) polymerase (PARP), reducing Bcl-2/Bax and Bcl-xl/Bad ratio, enhancing cellular reactive oxygen species (ROS) accumulation, triggering DNA damage, decreasing mitochondrial membrane potential (MMP), and leading cytochrome c release from mitochondria. Notably, complex Ru-1 showed low toxicity to developing zebrafish embryos. The obtained results suggest that these new synthetic complexes have the potential to be developed as low-toxicity agents for lung cancer treatment.